The west wing. The complete second season/ [videorecording (DVD)] - Schlamme, Thomas; Graves, Alex; Sheen, Martin; Spencer, John, 1946-2005; Whitford, Bradley (Warner Bros. Entertainment, 2018)
Follows the adventures of the staff and the inner workings of the Bartlet presidential administration.